Opportunities to improve cardiovascular health in the new American workplace - Eamon Y. Duffy; Pranoti G. Hiremath; Pablo Martinez-Amezcua; Richard Safeer; Jennifer A. Schrack; Michael J. Blaha; Erin D. Michos; Roger S. Blumenthal; Seth S. Martin; Miguel Cainzos-Achirica (Elsevier, 2021)
Adult working-class Americans spend on average 50% of their workday awake time at their jobs. The vast majority of these jobs involve mostly physically inactive tasks and frequent exposure to unhealthy food options. Traditionally, the workplace has been a challenging environment for cardiovascular prevention, where cardiovascular guidelines have had limited implementation. Despite the impact that unhealthy lifestyles at the workplace may have on the cardiovascular health of U.S. workers, there is currently no policy in place aimed at improving this. In this review, we discuss recent evidence on the prevalence of physical inactivity among Americans, with a special focus on the time spent at the workplace; and the invaluable opportunity that workplace-based lifestyle interventions may represent for improving the prevention of cardiovascular disease. We describe the current regulatory context, the key stakeholders involved, and present specific, guideline-inspired initiatives to be considered by both Congress and employers to improve the "cardiovascular safety" of US jobs. Additionally, we discuss how the COVID-19 pandemic has forever altered the workplace, and what lessons can be taken from this experience and applied to cardiovascular disease prevention in the new American workplace. For many Americans, long sitting hours at their job represent a risk to their cardiovascular health. We discuss how a paradigm shift in how we approach cardiovascular health, from focusing on leisure time to also focusing on work time, may help curtail the epidemic of cardiovascular disease in this country.